Copyright Legal Responsibility for Illustrated Literary Works (Comics) Published on Online Sites Without Author's Permission - Akyuwen, Rory Jeff; Labetubun, Muchtar Anshary Hamid; Pane, Alvian Febriawan (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Comics are also creations that are equally important in the copyright protection system. This is because the importance of protecting comics is not only related to the development of human culture and civilization, as well as supporting economic progress, but can also stimulate the creativi ty of creators with the existence of a comic copyright protection law.Purposes of the Research: Focuses on legal responsibility for comics that are published without permission from the creator, analysis of regulations and legal sanctions obtained for the creatorsParties who violate the copyright of comics by using online sites to take action against them.Methods of the Research: Using normative juridical research methods, or in other words normative legal research.Results of the Research: The results of this study are that the legal liability of parties or actors who publish copyrighted comics on online sites without the permission or approval of the Creator/Copyright Holder is civil and criminal liability, in civil liability, can be sued for compensation and in criminal liability. Legal protection for creators/copyright holders in the event that their comics are published on online sites without the consent of the copyright holder has the right to take legal action through litigation and non-litigation. These legal efforts are criminal and civil legal efforts.